PERBANDINGAN PRONOMINA PERSONA BAHASA INDONESIA DENGAN BAHASA MALAYSIA: TINJAUAN SEMANTIS - Aswan, Aswan; Idris, Nuny Sulistiany; Widia, Ida (Diksi, 2021)
Indonesian and Malaysian are languages that are often debated because they have similarities and similarities. This happens because Indonesian and Malaysian are rooted in Malay. Problems related to Indonesian and Malaysians are interesting to study. The topic discussed in this study is the use of Indonesian and Malaysian personal pronouns. The main objective of this study is to compare the use of Indonesian and Malaysian personal pronouns from a semantic point of view. That is, the authors compare them in terms of lexical meaning. This is because the root of a vocabulary is the meaning of the dictionary. In this study, the type of qualitative method with a descriptive approach was chosen as the data analysis method.. The data collected is in the form of first, second, and third personal pronoun vocabulary. The data sources for this study are Kamus Besar Bahasa Indonesia and Kamus Dewan Bahasa Malaysia. Based on the results of the study, it was found that the use of Indonesian and Malaysian pronouns had differences and similarities. The difference can be seen from the number of meanings. In Indonesian, there are as many as 15 meanings, while in Malaysia there are as many as 20 meanings. The similarities can be seen in each personal pronoun.